2018
DOI: 10.1093/pcp/pcy181
|View full text |Cite
|
Sign up to set email alerts
|

Capsicum annuum HsfB2a Positively Regulates the Response to Ralstonia solanacearum Infection or High Temperature and High Humidity Forming Transcriptional Cascade with CaWRKY6 and CaWRKY40

Abstract: The responses of pepper (Capsicum annuum) plants to inoculation with the pathogenic bacterium Ralstonia solanacearum and to high-temperature-high-humidity (HTHH) conditions were previously found to be coordinated by the transcription factors CaWRKY6 and CaWRKY40; however, the underlying molecular mechanism was unclear. Herein, we identified and functionally characterized CaHsfB2a, a nuclear-localized heat shock factor involved in pepper immunity to R. solanacearum inoculation (RSI) and tolerance to HTHH. CaHsf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 93 publications
0
32
0
Order By: Relevance
“…HSFB1 and HSFB2b repress the expression of HSFs, but positively impact the acquired thermotolerance [58]. Capsicum annuum HSFB2a forms a transcriptional cascade with CaWRKY6 and CaWRKY40 to positively regulate the response to high temperature and high humidity [59]. Guan et al [60] found that regulation of heat stress-responsive genes including HSFC1 and other HSFs by RCF2 and its interacting partner NAC transcription factor NAC019 is critical for thermotolerance in Arabidopsis.…”
Section: Ashsp268a-mediated Hsp/hsf Pathway and Plant Abiotic Stressmentioning
confidence: 99%
“…HSFB1 and HSFB2b repress the expression of HSFs, but positively impact the acquired thermotolerance [58]. Capsicum annuum HSFB2a forms a transcriptional cascade with CaWRKY6 and CaWRKY40 to positively regulate the response to high temperature and high humidity [59]. Guan et al [60] found that regulation of heat stress-responsive genes including HSFC1 and other HSFs by RCF2 and its interacting partner NAC transcription factor NAC019 is critical for thermotolerance in Arabidopsis.…”
Section: Ashsp268a-mediated Hsp/hsf Pathway and Plant Abiotic Stressmentioning
confidence: 99%
“…HSFB1 and HSFB2b repress the expression of HSFs, but positively impact the acquired thermotolerance [65]. Capsicum annuum HSFB2a forms a transcriptional cascade with CaWRKY6 and CaWRKY40 to positively regulate the response to high temperature and high humidity [66]. Guan et al [67] found that regulation of heat stress-responsive genes including HSFC1…”
Section: Ashsp268a-mediated Hsp/hsf Pathway and Plant Abiotic Stressmentioning
confidence: 99%
“…HSFB1 and HSFB2b repress the expression of HSFs, but positively impact the acquired thermotolerance [65]. Capsicum annuum HSFB2a forms a transcriptional cascade with CaWRKY6 and CaWRKY40 to positively regulate the response to high temperature and high humidity [66]. Guan et al [67] found that regulation of heat stress-responsive genes including HSFC1 and other HSFs by RCF2 and its interacting partner NAC transcription factor NAC019 is critical for thermotolerance in Arabidopsis.…”
Section: Ashsp268a-mediated Hsp/hsf Pathway and Plant Abiotic Stressmentioning
confidence: 99%